Henry Wade (1876–1955), pioneer of urological surgery, museum conservator and war veteran. (August 2019) - Gardner, Dugald
Henry Wade graduated in the Edinburgh Medical School in 1898 before spending two years with the British army during the Anglo-Boer war. Returning to this country, he joined Francis Caird, surgeon to the Edinburgh Royal Infirmary. Appointed Conservator of the museum of the Royal College of Surgeons of Edinburgh, Wade met young William Ford Robertson. In a study of experimental cancer they concluded that some neoplasms were caused by bacteria. Wade became increasingly recognised as an authority in urology. His growing practice was interrupted by the First World War. Already a member of the Royal Army Medical Corps, he served for five years in the Middle East, in Gallipoli and then with the army in an approach to Jerusalem. Resuming civilian life, Wade combined an extensive urological practice with membership of the Council of the RCSEd. He became President in 1935. Married in 1924, his wife died four years later after an operation by a colleague, David Wilkie. Director of Surgery to the Scottish Emergency Medical Service when the Second World War broke out, Wade was made a Knight Bachelor in 1946. He died in 1955.